PERTANGGUNGJAWABAN PENGELOLAAN KEUANGAN DANA BANTUAN SOSIAL APBD PADA PROYEK PERCETAKAN SAWAH DI KABUPATEN LANDAK - FETTY HIMAWATI, SH NPM.A2021151095, Jurnal Mahasiswa s2 Hukum Untan (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACT This thesis discusses the accountability of financial management of social assistance fund of APBD At Rice Field Printing Project in Regency Landak. The method used in this research is Normative-Sociological approach. The conclusion of this thesis is that the financial management of social aid fund of apbd in paddy field printing project in Landak District with grant budget allocation and social assistance of paddy field in revenue and expenditure budget structure of district of hedgehog shows in practice still open space problem inaccuracy Appraisal feasibility assessment of authorized officers assessing and objectivity of reporting of their implementation by the Institution / Organization and / or Social Organization. Especially when applied parameters of Government Accounting Standards in accordance with the provisions applicable in the field of State Financial Management. The dominant factor that inhibits the management of grant budgets and paddy-social aid in the Landak State Budget Structure Structure is the difficulty of defining social assistance expenditures, as it can be widely interpreted, thus allowing for errors in determining the objectives and objects of grant aid and social assistance, The occurrence of social assistance expenditure is budgeted into non-social expenditure, or otherwise non-social assistance expenditure is budgeted into social assistance expenditure, the opportunity for non-conformity between the budget and its implementation occurs, social assistance spending is not channeled to activities related to social protection and social welfare And open opportunities for non-conformity between budget and accountability or unsupported with sufficient evidence. Recommendations: guidance and reporting in the framework of the implementation of grants and social assistance is important to the beneficiaries, especially regarding administrative and technical aspects, considering that the funds used are the absolute government funds must be held accountable. Coaching can be done in stages in accordance with the main tasks and functions of each satker. Guidance and guidance undertaken for the purpose of distributed social assistance can provide benefits in accordance with the intended target. Key Words: The Role of Government, Providing, Health Services, Prisoners. 2 ABSTRAK Tesis ini membahas tentang pertanggungjawaban pengelolaan keuangan dana bantuan sosial APBD Pada Proyek Percetakan Sawah di Kabupaten Landak. Metode yang digunakan dalam penelitian ini adalah pendekatan Normatif-Sosiologis. Adapun kesimpulan dari tesis ini ada bahwa Bahwa pengelolaan keuangan dana bantuan sosial apbd pada proyek percetakan sawah di Kabupaten Landak dengan alokasi anggaran belanja hibah dan bantuan sosial cetak sawah dalam struktur anggaran pendapatan dan belanja daerah kabupaten landak menunjukkan dalam praktiknya masih tebuka ruang-ruang masalah ketidakakuratan penilaian kelayakan peruntukan dari pejabat yang berkewenangan menilai dan obyektivitas pelaporan pelaksanaannya oleh Lembaga/Organisasi dan atau Organisasi Kemasyarakatan. Terutama bila diterapkan parameter Standar Akuntansi Pemerintahan sesuai ketentuan yang berlaku di bidang Pengelolaan Keuangan Negara. Faktor dominan yang menghambat pengelolaan anggaran belanja hibah dan bantuan sosial cetak sawah dalam Struktur APBD Kabupaten Landak, adalah Kesulitan mendefinisikan belanja bantuan sosial, karena dapat ditafsirkan secara luas, sehingga membuka peluang terjadinya kesalahan dalam menentukan sasaran dan obyek bantuan hibah dan bantuan sosial, terbuka peluang terjadinya terjadinya belanja bantuan sosial dianggarkan ke dalam belanja non bantuan sosial, atau sebaliknya belanja non bantuan sosial dianggarkan ke dalam belanja bantuan sosial, terbuka peluang terjadinya ketidaksesuaian antara anggaran dan pelaksanaannya, belanja bantuan sosial tidak disalurkan untuk kegiatan yang berkaitan dengan perlindungan sosial dan kesejahteran sosial dan terbuka peluang terjadinya ketidaksesuaian antara anggaran dan pertanggungjawaban atau tidak didukung dengan bukti-bukti yang memadai. Rekomendasi : pembinaan dan pelaporan dalam rangka pelaksanaan hibah dan bantuan sosial penting dilakukan kepada penerima bantuan, terutama menyangkut aspek administratif dan teknis mengingat dana yang digunakan merupakan dana pemerintah yang mutlak harus ada pertanggungjawabannya. Pembinaan dapat dilakukan secara berjenjang sesuai dengan tugas pokok dan fungsi masing-masing satker. Pembinaan dan bimbingan yang dilakukan bertujuan untuk bantuan sosial yang disalurkan dapat memberikan manfaat sesuai dengan sasaran yang diharapkan. Kata Kunci: Peran Pemerintah, Memberikan, Pelayanan Kesehatan, Narapidana.